1995
DOI: 10.1159/000168849
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Simultaneous Renal Clearances of True Endogenous Creatinine and Subcutaneously Administered lothalamate in Man

Abstract: 125I-iothalamate and true endogenous creatinine clearances, measured over two short collections periods of 1 and 2 h, were compared simultaneously in 70 patients with a variety of renal diseases and a wide range of renal function. Reproducibility of the iothalamate clearance was 18.5 % and that of the creatinine clearance 12.2%. The slope of the regression was not significantly different from 1 (95% confidence interval, CI, 0.964-1.155) for the whole group, nor in any subgroup chosen. The intercept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, data from several studies demonstrated good agreement between creatinine clearance and 'true filtration markers'. These studies reported a close correlation between creatinine clearance and inulin [20], creatinine clearance and 125 I-iothalamate [21][22][23], and creatinine clearance and 99m Tc-DTPa [24,25] at all levels of renal function. Furthermore a metaanalysis found that creatinine clearance accurately detected even moderate GFR reduction and reflected changes in GFR well [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, data from several studies demonstrated good agreement between creatinine clearance and 'true filtration markers'. These studies reported a close correlation between creatinine clearance and inulin [20], creatinine clearance and 125 I-iothalamate [21][22][23], and creatinine clearance and 99m Tc-DTPa [24,25] at all levels of renal function. Furthermore a metaanalysis found that creatinine clearance accurately detected even moderate GFR reduction and reflected changes in GFR well [26].…”
Section: Discussionmentioning
confidence: 99%
“…Using creatinine clearance as reference method to assess the performance of serum cystatin C and serum creatinine, we are aware that creatinine clearance can result in an inaccurate estimate of GFR [2,22,261. However, good agreement between creatinine clearance and "true" markers of GFR as inulin [3], 1251-iothalamate [16] and 99mTc-DTPA clearance [17,20] at all levels of renal function was reported. Therefore, we used creatinine clearance as a reasonably accurate estimate of GFR, although we recognize that creatinine clearance has limitations and does not exactly measure GFR.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, creatinine clearance is used, even though it is well known that creatinine clearance usually exceeds GFR. The relationship between these two measures in patients with GFR values Յ10 ml/min, according to 13 published reports (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), is depicted in Figure 2, including two studies (38,45) in patients on dialysis (many other publications do not report their data in sufficient detail to permit even approximate conversion of their graphical observations to numerical estimates). The ratio of creatinine clearance to simultaneously measured GFR in these 115 observations varies considerably; the mean is 1.34 Ϯ 0.43 (SD).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of creatinine clearance to measured GFR in severe renal failure (GFR Ͻ10 ml/min), according to 115 observations, approximately graphed from 13 published studies (32-45), including two (37,44) in patients on dialysis. Wide variation in the ratio is seen.…”
Section: Figurementioning
confidence: 99%